The psychometric properties of the strengths and difficulties questionnaire for children from refugee backgrounds in Australia - Essex, Ryan (My University, 2019)
This paper discusses the psychometric properties of the strengths and difficulties questionnaire for children from refugee backgrounds in Australia.
Clinical Psychologist
Keywords: Adolescents and youth; Childhood and child development; Health and wellbeing; Migration and settlement